e-DSMES DALAM MENINGKATKAN MANAJEMEN PERAWATAN DIRI PENDERITA DIABETES MELITUS DI MASA PANDEMI COVID-19 - Toar, Juwita Moreen; Rooroh, Victor Giovannie Xaverison; Pontoh, Fransisca Joanet (JURNAL KEPERAWATAN, 2024)
Abstract Background: The COVID-19 pandemic has impacted access to healthcare services and accelerated the adoption of technology in managing chronic diseases such as diabetes mellitus. Diabetes Self-Management Education and Support (DSMES) utilizing technology has become increasingly important in the context of social restrictions and changes in healthcare access, providing knowledge and support to individuals with diabetes to manage their condition independently. Self-care capabilities can optimize metabolic control, prevent complications, and improve the quality of life for diabetes patients. Education for diabetes patients during the COVID-19 pandemic is essential so that an effective educational model intervention strategy is needed.Objective: This study aims to determine the effect of electronic Diabetes Self-Management Education and Support (e-DSMES) on the self-care abilities of individuals with type 2 diabetes mellitus during the COVID-19 pandemic. Methods: The research design used was a pre-experimental design with a one-group pre-post test and the sampling technique is simple random sampling. A total of 20 individuals with type 2 diabetes mellitus enrolled in Prolanis at the Wenang Community Health Center in Manado participated in the e-DSMES program for 4 weeks. Data were collected using the Diabetes Self-Management Questionnaire (DSMQ) to measure respondents' self-care abilities. Results: Data analysis using a paired t-test showed a significant difference in the average self-care management scores before and after the implementation of e-DSMES (p < 0.05 and CI does not include zero).Conclusion: The implementation of e-DSMES can be an effective strategy in improving health outcomes for individuals with diabetes during the pandemic and other social restriction situations. Keywords: diabetes education program; telehealth; diabetes; selfcare management; covid 19